Structural and mechanistic studies of quinone oxidoreductase II : NQO2 - Refaey, Rana Hosny (2011)
Flavoenzymes are a widely diverse group of enzymes that are able to catalyze a variety of different chemical reactions. A growing interest in flavoenzymes capable of reducing aromatic nitro groups may be attributed to their ability to reduce anticancer prodrugs such as CB 1954. Similarly, quinine oxidoreductases are able to activate anticancer prodrugs such as mitomycin derivatives by reducing the quinone derivative to the hydroxyl derivative. Some oxidoreductases are able to reduce nitro aromatic compounds. These enzymes may be either mammalian such as NQO1 and NQO2 which are over expressed in certain cancerous cells or bacterial which can be introduced into the cancerous growth. The bacterial nitroreductases have been previously well characterized and were found to share several similarities. On the other hand, other nitro reducing enzymes have not been investigated to determine the presence of any shared similarities. Another aim of this thesis is to identify the differences between the structure of the oxidized and reduced forms of NQO2. The similarities shared between the flavoenzymes which are known to reduce nitroaromatic compounds to their hydroxylamine or amine derivative were investigated in this thesis. Both the sequences and 3D structures of the selected proteins were compared and investigated using a variety of bioinformatics tools such as sequence and structure alignment, in addition to homology modelling. It was discovered that there are several aromatic residues conserved in different positions, relative to the flavin cofactor, in the catalytic sites of the proteins. The 3D structure of the reduced NQO2 was determined using X-ray crystallography. The oxidized and reduced protein structures were compared to determine the structural differences. The expression, purification and crystallization of the NQO2 protein, as well as the reduction of the protein crystals are described in this work. The determination of the structure of the reduced protein provided new insights into the mechanism of electron transport to and from the flavin cofactor. Moreover, kinetics studies were undertaken on the purified NQO2 protein using fluorescence spectroscopy. These resulted in the identification of several new substrates for NQO2.